2014
DOI: 10.11648/j.sjcm.20140306.13
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Cutaneous Leishmaniasis and the Pattern of Lesions in Ochollo Primary School Students, Ochollo, Southwestern Ethiopia

Abstract: Background: Leishmaniasis is a vector borne disease caused by the obligate intracellular protozoan leishmania.Objective:To assess the prevalence of cutaneous leishmaniasis and pattern of lesions in Dega Ochollo primary school students, Ochollo, Southwestern Ethiopia. Methods: A cross-sectional study was carried out among 523 school children aging between 6 to 25 years. The students were physically examined for the presence of scar and active lesions. Skin slit and blood were collected from students with suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 18 publications
9
54
0
Order By: Relevance
“…A lot of literatures have also proven that a tremendous importance for greatly affecting the incidence of visceral leishmaniasis. This result is consistent with what was discussed in the literature review by Bugssa, et al [9] that showed travel history to the endemic area was significant factor for the incidence of visceral leishmaniasis disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A lot of literatures have also proven that a tremendous importance for greatly affecting the incidence of visceral leishmaniasis. This result is consistent with what was discussed in the literature review by Bugssa, et al [9] that showed travel history to the endemic area was significant factor for the incidence of visceral leishmaniasis disease.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, elevation and rainfall were the significant factors for visceral leishmaniasis disease within the district at 95% confidence level, which is supported by [9][10][11].…”
Section: Discussionsupporting
confidence: 66%
“…Social exclusion of CL patients has also been reported elsewhere in literature [8]. In its most extreme form, students equated CL with ‘social death’ due to the visibility of CL scars, which has also been reported by other authors [2729]. If a CL scar is located on the face, it is perceived as a barrier for marriage and in this traditional society, this can imply ‘social death’ for women.…”
Section: Discussionmentioning
confidence: 58%
“…CL particularly occurs in foci on the mountain slopes of the Ethiopian Rift Valley, ranging from North to Southwest and South to Northeast in the country. The described foci are all situated at altitudes ranging between 1700-2700 m and are located in four regional states: Southern Nations, Nationalities and Peoples' Region (SNNPR), Amhara, Tigray and Oromia, and Addis Ababa city administration [6,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Ochollo is a well-known CL focus at about 2100 m in southwestern Ethiopia and is considered a model village for research investigating the transmission dynamics of CL [6,9,15]. The area has a rough topography and is characterized by steep slopes, many rocks and basalt cliffs with caves, providing the ideal habitat for P. pedifer and the animal reservoir of the infection, hyraxes [16].…”
Section: Introductionmentioning
confidence: 99%